2013
DOI: 10.4103/2045-080x.119066
|View full text |Cite
|
Sign up to set email alerts
|

Career preferences and attitude of first year Doctor of Pharmacy students toward pharmacy profession

Abstract: Objectives:To evaluate first year Doctor of Pharmacy (PharmD) students' career preferences, factors involved in this selection, and attitude toward pharmacy profession. Materials and Methods: First year PharmD students enrolled at University of Peshawar were surveyed through administration of predesigned questionnaire. The anonymous questionnaire sought students' opinions on the factors influencing their career preferences, attitude and knowledge of pharmacy profession, and importance of pharmacy profession in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…This observation is corroborated by a study carried out in Pakistan which showed that more than half of the pharmacy graduates preferred non-pharmacy jobs. 4 In this study, nearly half of the respondents indicated interest to practice outside Nigeria. This is not surprising given the exodus of professionals, including pharmacists, from their native countries that have been witnessed in recent years.…”
Section: Characteristicsmentioning
confidence: 70%
See 1 more Smart Citation
“…This observation is corroborated by a study carried out in Pakistan which showed that more than half of the pharmacy graduates preferred non-pharmacy jobs. 4 In this study, nearly half of the respondents indicated interest to practice outside Nigeria. This is not surprising given the exodus of professionals, including pharmacists, from their native countries that have been witnessed in recent years.…”
Section: Characteristicsmentioning
confidence: 70%
“…Several studies have been done on the development of pharmacy education and pharmacy practice in some parts of the world including Malaysia, 3,4 Pakistan, 5 Jordan 6 and Sudan. 7 As with most countries where pharmaceutical care is in its early stage of development, a common deficiency noted in the pharmacy curriculum of the aforementioned countries is a lack of clinical training.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of our research are related to different investigations that decided lacking information and awareness of college scholars toward biotechnology before they get admission [26][27][28][29][30]. A vast majority of studies were pointing to mindfulness and information toward biotechnology among the overall population.…”
Section: Discussionmentioning
confidence: 95%
“…The study instrument was a self-administered structured questionnaire. Items for this questionnaire were adapted from instruments used in similar studies in other countries (Hasan et al, 2010;Salman et al, 2013;Shakeel et al, 2013;Loo et al, 2017;James et al, 2018;Alhomoud et al, 2019;AlQudah et al, 2019). After the instrument was designed, it was assessed for face and content validity by two clinical pharmacy lecturers and found to be adequate.…”
Section: Study Instrumentmentioning
confidence: 99%
“…These options could include careers in hospital pharmacy, community pharmacy, industrial pharmacy, veterinary pharmacy and so on. Several studies have been carried out in many countries to assess career options and the factors affecting these choices among pharmacy students (Hasan et al, 2010;Ubaka et al, 2013;Shakeel et al, 2013;Salman et al, 2013;Loo et al, 2017;James et al, 2018;Alhomoud et al, 2019;Al-Qudah et al, 2019;Jarab et al, 2021). As would be expected, most of these studies have reported varying results (both for career choices and the factors influencing these choices).…”
Section: Introductionmentioning
confidence: 99%